Unreal Engine 4 Shaders and Effects Cookbook : Over 70 recipes for mastering post-processing effects and advanced shading techniques /: Over 70 recipes for mastering post-processing effects and advanced shading techniques. (2019) - Brenlla Ramos, Brais; P. Doran, John
No abstract available